Assessing the increase in soil moisture storage capacity and nutrient enhancement of different organic amendments in paddy soil - Haque, Ahmad Numery Ashfaqul; Uddin, Md. Kamal; Sulaiman, Muhammad Firdaus; Mohd Amin, Adibah; Hossain, Mahmud; Zaibon, Syaharudin; Mosharrof, Mehnaz (Multidisciplinary Digital Publishing Institute, 2021)
Increasing soil moisture storage capacity is a strategy that can be implemented to minimize the use of water in paddy rice cultivation. Organic materials from different sources have the potential to increase soil moisture storage and nutrient enrichment. An incubation study was conducted to evaluate the incorporation of five selected organic amendments—as follows: rice husk biochar (RHB), oil palm empty fruit bunch biochar (EFBB), compost (COMP), rice husk ash (RHA), and oil palm bunch ash (PBA), with a control (no amendment) on soil moisture storage and some chemical properties of soil. The soil was incubated with five amendments for 60 days and sampled at 15-day intervals. After completion of the incubation, a greater extent of gravimetric water content was observed from RHB (0.46 g g−1) and EFBB (0.45 g g−1) followed by compost (0.40 g g−1). The addition of organic amendments significantly influenced soil chemical properties. Maximum soil pH was altered by PBA followed by EFBB compared to its initial value (5.01). The inclusion of EFBB finally contributed to the highest amount of total carbon (7.82%) and nitrogen (0.44%). The addition of PBA showed the highest available P and exchangeable K followed by RHB when compared with the amendments. The results indicated that RHB, EFBB, and compost retain more soil moisture compared to ash sources and added soil nutrients, indicating their potential to improve the chemical and hydrological properties of paddy soil.